Fatigue and anisotropic behavior of wire-arc additive manufactured TC17 titanium alloy - Banglong Yu; Zhihao Chen; Ping Wang; Yong Liu; Xiaoguo Song; Pingsha Dong (Journal of Materials Research and Technology, 2024)
Wire-arc additive manufacturing (WAAM) was used in aeronautical engineering due to its low equipment cost and ability to create complex shapes. However, the fatigue behavior of WAAM titanium alloy, specifically for low cycle fatigue (LCF), was poorly studied. This paper investigated the microstructure and mechanical behavior of WAAM TC17 in both vertical and horizontal orientations. Fully reversed LCF tests were conducted on specimens with varying strain amplitudes from ±0.4 % to ±1.2 %. The results found that the ultimate tensile and yield strength were similar for both vertical and horizontal samples, but the elongation in the horizontal orientation was approximately 60 % lower than that in the vertical orientation. Considering the cyclic loading behavior, both vertical and horizontal samples exhibited cyclic softening characteristics at high strain amplitudes (0.8%–1.2 %). Additionally, the cyclic softening rate (CSR) of horizontal samples exhibited a higher than that of vertical samples at high strain amplitude. The LCF cracks of WAAM TC17 were initiated from the surface and internal defects of the samples. The LCF performance of the horizontal samples was found to decrease than that of vertical samples. Specifically, the fatigue performance of the horizontal samples is lower by 36.7 % compared to the vertical samples when the number of cycles is 103.